The Neutron Star—Black Hole Connection 2001
DOI: 10.1007/978-94-010-0548-7_34
|View full text |Cite
|
Sign up to set email alerts
|

The Chandra X-Ray Observatory (CXO)

Abstract: The Chandra X-Ray Observatory (CXO), the x-ray component of NASA's Great Observatories, was launched early in the morning of 1999, July 23 by the Space Shuttle Columbia. The Shuttle launch was only the first step in placing the observatory in orbit. After release from the cargo bay, the Inertial Upper Stage performed two firings, and separated from the observatory as planned. Finally, after five firings of Chandra's own Integral Propulsion System -the last of which took place 15 days after launch -the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
25
0
2
Order By: Relevance
“…Our emphasis will thus be on results from the Chandra X-ray Observatory (hereafter Chandra; e.g., Weisskopf et al 2000), the X-ray Multi-Mirror Mission (hereafter XMM-Newton; e.g., Jansen et al 2001), and the Nuclear Spectroscopic Telescope Array (hereafter NuSTAR; e.g., Harrison et al 2013). The new results from these missions rest squarely upon a rich heritage of X-ray survey studies with several superb earlier X-ray missions, as briefly described in, e.g., Section 3.1.…”
mentioning
confidence: 99%
“…Our emphasis will thus be on results from the Chandra X-ray Observatory (hereafter Chandra; e.g., Weisskopf et al 2000), the X-ray Multi-Mirror Mission (hereafter XMM-Newton; e.g., Jansen et al 2001), and the Nuclear Spectroscopic Telescope Array (hereafter NuSTAR; e.g., Harrison et al 2013). The new results from these missions rest squarely upon a rich heritage of X-ray survey studies with several superb earlier X-ray missions, as briefly described in, e.g., Section 3.1.…”
mentioning
confidence: 99%
“…Properties of the ∼3.5 keV line reported by[70,71]. For their analysis, the authors of[70,71] use different Xray datasets observed by MOS[73] and PN[72] cameras on-board XMM-Newton observatory[74] and ACIS instrument[76] on-board Chandra observatory[77]. All error bars are at 1σ (68%) level.…”
mentioning
confidence: 99%
“…²ÂÔÔÏÂÕÓËÄÂÇÕÔâ ÕÂÍÉÇ ÄÑÊÏÑÉÐÑÔÕß ÕÑÅÑ, ÚÕÑ àÕË âÓÍËÇ ËÔÕÑÚÐËÍË âÄÎâáÕÔâ ÏËÍÓÑÍÄÂÊÂÓÂÏË, ÓÇÎâÕËÄËÔÕÔÍËÇ AEÉÇÕÞ ÍÑÕÑÓÞØ ÐÂ-ÒÓÂÄÎÇÐÞ Ð ÐÂÃÎáAEÂÕÇÎâ [60,61]. £ àÕÑÏ ÔÎÖÚÂÇ ÏÂÔÔÞ ÓÇÎâÕËÄËÔÕÔÍËØ ÑÃÝÇÍÕÑÄ ÒÑÓâAEÍ ÐÇÔÍÑÎßÍËØ M .¯Ç-AEÂÄÐÇÇ ÑÒÕËÚÇÔÍÑÇ ÑÕÑÉAEÇÔÕÄÎÇÐËÇ ÑAEÐÑÅÑ ËÊ ÕÂÍËØ ÑÃÝÇÍÕÑÄ [61] ÒÑAEÍÓÇÒÎâÇÕ àÕÖ ÅËÒÑÕÇÊÖ.…”
Section: ®çõñAeþ òñëôíâ úçóðþø Aeþóunclassified